Cutinases fúngicas: propriedades e aplicações industriais - Pio, Tatiana Fontes (2008)
Cutinases (EC 3.1.1.74) are also known as cutin hidrolases. These enzymes share catalytic properties of lipases and esterases, presenting a unique feature of being active regardless the presence of an oil-water interface, making them interesting as biocatalysts in several industrial processes involving hydrolysis, esterification and trans-esterification reactions. They are also active in different reaction media, allowing their applications in different areas such as food industry, cosmetics, fine chemicals, pesticide and insecticide degradation, treatment and laundry of fiber textiles and polymer chemistry. The present review describes the characteristics, potential applications and new perspectives for these enzymes.